Basic writings : from Being and Time(1927) to The Task of Thinking (1964) - Heidegger, Martin (Routledge, 2012)
Few philosophers have had more influence on the shape of western philosophy after 1900 than Martin Heidegger. Basic Writings offers a full range of this profound and controversial thinker's writings in one volume, including: